MENINGKATKAN KARAKTERMELALUI PEMBELAJARAN OLAHRAGA PADA MI UNGGULAN MUHAMMADIYAH LEMAHDADI BANGUNJIWO KASIHAN BANTUL YOGYAKARTA - Muhammad Fatkhan Muallifin (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
The lack of character education makes students less responsible. Students just want to get good grades without having to learn by cheating. It is necessary to improve student character education so that they can have good behavior without having to take actions that are out of social values. Not only in terms of learning but also behavior at home and in madrasas. MIU Muhammadiyah is a madrasa that has good outcomes. Therefore, the researcher raises the problem of how MIU Muhammadiyah Lemahdadi Bangunjiwo Kasihan Bantul Yogyakarta can improve character through learning sports for students. This study used a qualitative approach with field research. The data collection techniques used were observation, interviews, and documentation. The selected data sources, namely the Head of Madrasah, Teachers and Students are strengthened with relevant documents to produce more valid data. The results of the analysis show that efforts to improve the character of MIU Lemahdadi students can be realized in several forms of methods, namely giving rewards, giving praise, providing added value, sanctions or punishments, creating healthy competition, instilling a sense of responsibility for an obligation according to student needs.